2022
DOI: 10.1590/1980-220x-reeusp-2021-0568en
|View full text |Cite
|
Sign up to set email alerts
|

Clinical indicators, nursing diagnoses, and mortality risk in critically ill patients with COVID-19: a retrospective cohort

Abstract: Objective: To identify clinical indicators and nursing diagnoses with the highest risk of mortality in critically ill patients with COVID-19. Method: Retrospective cohort with the population of adults and elderly people with COVID-19 from an Intensive Care Unit. Categorical variables were described using absolute and relative frequencies and risk factors for mortality using Cox regression, with a confidence interval of 95%. Results: The main clinical indicators of COVID-19 patients were dyspnea, fever, fatig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The findings of this study align with previous research conducted with patients affected by SARS-CoV-2, which also reported a high prevalence of risk nursing diagnoses such as Risk for adult pressure injury and Risk for infection [ [4] , [5] , [6] ]. Research conducted in the Brazilian Amazon region involving ICU patients hospitalized with COVID-19 complications from March to December 2020 revealed that the nursing diagnosis "Risk for infection" was documented in 100% of the nurses' records and "Risk for adult pressure injury" was documented in 97% of them [ 5 ].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The findings of this study align with previous research conducted with patients affected by SARS-CoV-2, which also reported a high prevalence of risk nursing diagnoses such as Risk for adult pressure injury and Risk for infection [ [4] , [5] , [6] ]. Research conducted in the Brazilian Amazon region involving ICU patients hospitalized with COVID-19 complications from March to December 2020 revealed that the nursing diagnosis "Risk for infection" was documented in 100% of the nurses' records and "Risk for adult pressure injury" was documented in 97% of them [ 5 ].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, it was observed that in many hospital units, there is a tendency to adopt a more free-form approach to nursing care, where the care plan is formulated based on the individual nurse's clinical experiences. This practice reflects a resistance to standardization, which goes against the principles of the SNC [ 5 ]. Overcoming this challenge requires collaborative efforts from both health management and the nursing profession to promote the adoption of SNTs in nursing care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 is a viral respiratory disease with increasing mortality with increasing age of patients and occurring comorbidities such as obesity, diabetes and immune deficiency [ 15 , 16 , 17 ]. The disease has typical indicators of shortness of breath (dyspnea), fever, fatigue and cough, but other manifestations can occur depending on the variant of COVID-19 and individual dispositions, and some post-COVID-19 syndromes can remain even after the infection resolves [ 18 , 19 , 20 , 21 , 22 , 23 ]. An increase in inflammatory cytokines and the appearance of symptoms after inflammation is also typical for COVID-19 [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Current Point-of-care Tests For Covid-19mentioning
confidence: 99%